Estudo sistêmico das inter-relações dos construtos que influenciam a satisfação residencial visando à elaboração de um modelo a partir da percepção cognitiva do indivíduo - Faganello, Adriana Macedo Patriota (2019)
Designing is something that is done in the present with the intention of having it built in the future, which is a complex and transdisciplinary act, therefore require the systematic introduction of diverse perspectives to achieve effective responses. Thus, there is a search to reduce the repetition of errors, not only meeting the technical standards, but also aiming at continuous improvement, considering the environment user's quality of life and satisfaction. The objective of this research is to understand the performance of the various the individual and the environment factors intrinsic through cognitive perception and how these factors interrelate in the residential satisfaction model. The research adopted the hypothetical deductive method through a systemic and transdisciplinary approach, using the survey as a research instrument, using the methodology of systemography to construct the general systemic model of residential satisfaction and as a statistical analysis tool the correlation analysis, factor analysis and structural equation modeling. After understanding the aspects that encompass the cognitive perception of the environment along with the understanding of how the process of environmental assessment takes place, the conceptual theoretical model of residential satisfaction was built and empirically tested considering the exogenous variables: sociodemographic characteristics, life history, psychological characteristics, current housing characteristics and costs, and the following endogenous variables: life experience, performance, expectation, perceived value, satisfaction and potential action. After multivariate analysis results, an empirical model was proposed, tested, compared and adjusted, resulting in the final model of residential satisfaction. The final model suggests that the main predictors of residential satisfaction are: Life Cycle, Socioeconomic Characteristics, Costs, Lifestyle, Expectation, Housing Performance and Surrounding Performance. Finally, this work contributed to the construction of knowledge about the interrelationships of the constructs that influence Residential Satisfaction, understanding that the correct feedback and control of a project bring greater efficiency and benefits to its users.